2002
DOI: 10.1002/bit.10394
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation kinetics of well and poorly differentiated human prostate cancer cells

Abstract: Aggregation of attachment-dependent animal cells represents a series of motility, collision, and adhesion events applicable to such diverse fields as tissue engineering, bioseparations, and drug testing. Aggregation of human prostate cancer cells in liquid-overlay culture was modeled using Smoluchowski's collision theory. Using well (LNCaP) and poorly differentiated (DU 145 and PC 3) cell lines, the biological relevance of the model was assessed by comparing aggregation rates with diffusive and adhesive proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 27 publications
5
47
0
1
Order By: Relevance
“…However, in another study comparing well-and poorly differentiated human prostate cancer cells, Enmon et al [18] have observed similar differences in the rates of spheroid formation. They found that the increased rate in spheroid formation was correlated with an increased expression level of E-cadherins.…”
Section: Binding-dependent Dynamics Of N-cadherinmentioning
confidence: 83%
“…However, in another study comparing well-and poorly differentiated human prostate cancer cells, Enmon et al [18] have observed similar differences in the rates of spheroid formation. They found that the increased rate in spheroid formation was correlated with an increased expression level of E-cadherins.…”
Section: Binding-dependent Dynamics Of N-cadherinmentioning
confidence: 83%
“…This study suggests that filopodia have additional roles in culture. Liquid-overlay culture generates spheroids of cancer cells used for drug testing [14]. The cells preferentially attached to each other rather than to the attachment-limiting agar substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Chambers were either pretreated with an attachment-limiting substrate, agar (liquid-overlay culture), or used without a coating (monolayer culture). For the former, the chambers were covered with a thin layer (1 mm) of 0.25% agar (Invitrogen, Carlsbad, CA) prepared in serum-free GTSF-2 medium [14]. The inoculum for these cultures consisted of 2.0 ×10 4 cells/cm 2 in 2 ml of complete GTSF-2.…”
Section: Cell Culturementioning
confidence: 99%
“…Liquid-overlay cultures were prepared by solidifying a mixture of 1% agar (Invitrogen, Carlsbad, CA) in 8-ml serum-free GTSF-2 medium within 100 mm × 20 mm petri dishes (Becton Dickinson Labware, Franklin Lakes, NJ) as described in Enmon et al [15]. The inoculum for these static cultures consisted of 1.7 × 10 5 cells/ml in 8-ml of complete GTSF-2.…”
Section: Cell Cultivationmentioning
confidence: 99%